]Performance of Waste Stabilisation Ponds in the Eastern Cape Province - Tolobisa, Gcina (Department of Civil Engineering, 2023)
Water is a scarce natural resource, which requires to be treated with much care and importance. It is a finite resource and should be used sparingly. The process of treating domestic wastewater varies from ponds to the more advanced system, namely the activated sludge system. The main purpose of wastewater treatment is the reduction of pathogenic contamination, coliform bacteria, suspended solids, oxygen demand, and nutrient enrichment. The application or use of stabilisation ponds, as a part of the wastewater treatment process, depends on, among other factors, the influent loading and climate conditions. Waste Stabilisation Ponds (WSPs) are used to biologically treat domestic wastewater or industrial wastewater. The present study focuses on the treatment of domestic wastewater by using the WSPs in the absence of mechanical and electrical equipments. Different countries use different methods of pond design or WSP sizing and different parameters to ensure that the effluent discharge guidelines of the Department of Water and Sanitation (DWS) and World Health Organisation (WHO) are met. There are insufficient literature studies focusing on the design models and water quality data that can be used for sizing the WSPs in South Africa. There is a requirement for a study that can compare the existing WSP design models in different countries and check their suitability for South Africa, particularly their applicability to provinces with respect to climate and domestic wastewater quality. The comparison between the WSP design models will assist the process designers in the early stages of projects, particularly in the feasibility study stages (Scenario 1). The objective of the present study is to perform a comprehensive review of the use of WSPs in domestic wastewater treatment, their design and operating requirements for optimal performance, and the existing mathematical models used to virtually replicate the WSP treatment processes. Also considered is the development of a simplified model to demonstrate its application as a tool for the effective design of WSPs, including a case study of a WSP in the Eastern Cape (EC).